1988
DOI: 10.1051/lait:198828
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Brucella abortus in ripened soft cheese made from naturally infected cow's milk

Abstract: SummaryMilk from eigh heifers experimentally inoculated with a virulent strain of Brucella abortus, and excreting large numbers ofthese bacteria at calving, was used to make three successive batches of a soft, camembert-type, cheese. Lactic fermentation was induced by a Streptococcus lactis and S. cremoris starter that caused the pH to fall to 4.5-4.6 after 20 hours. Surface inoculation of the curd with Penicillium caseicolum was performed before ripening at 12 oc. Brucella were enumerated by plating milk or l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 2 publications
0
9
0
2
Order By: Relevance
“…4.2 log cfu g À1 in curd; 4.3 log cfu g À1 in curd out of mould Storage at 12 C; 3.0 log cfu g À1 in cheese at day 5, 1.5 log cfu g À1 in cheese at day 8, 1.3 log cfu g À1 in cheese at day 12, 1.1 log cfu g À1 in cheese at day 15, 0.4 log cfu g À1 in cheese at day 18, 0 cfu g À1 in cheese at day 22 Plommet et al (1988) Inoculation of À0.7 and 0.3 log cfu cm À2 of L. monocytogenes Storage at 4 C; increase after day 28; increase to 2.96 log cfu g À1 at day 60 (low inoculum); increase to 4.55 log cfu g Inoculation of 7.1e8.7 log cfu g À1 of VTEC O157 and O26 of curd;…”
mentioning
confidence: 99%
“…4.2 log cfu g À1 in curd; 4.3 log cfu g À1 in curd out of mould Storage at 12 C; 3.0 log cfu g À1 in cheese at day 5, 1.5 log cfu g À1 in cheese at day 8, 1.3 log cfu g À1 in cheese at day 12, 1.1 log cfu g À1 in cheese at day 15, 0.4 log cfu g À1 in cheese at day 18, 0 cfu g À1 in cheese at day 22 Plommet et al (1988) Inoculation of À0.7 and 0.3 log cfu cm À2 of L. monocytogenes Storage at 4 C; increase after day 28; increase to 2.96 log cfu g À1 at day 60 (low inoculum); increase to 4.55 log cfu g Inoculation of 7.1e8.7 log cfu g À1 of VTEC O157 and O26 of curd;…”
mentioning
confidence: 99%
“…Gilman et al (1946) observed B. abortus in samples of cheddar cheese with 6 months of storage. Plommet et al (1988) assessed B. abortus in camembert cheese manufactured from cows' milk infected experimentally and reported that the initial load in the cheese (3-4 log CFU g -1 ) was reduced to undetectable levels after 18 days at 12°C. Méndez-González et al (2011) reported the influence of maturation temperature of cheese on the survival of B. melitensis, which was recovered up to 50 days after maturation at 4°C and up to 20 days after maturation at 24°C.…”
Section: Resultsmentioning
confidence: 99%
“…Após a acidificação, as contagens diminuíram consistentemente a uma taxa tal que nenhuma Brucella pode ser recuperada após o 18º dia, seja por cultura bacteriológica ou por administração experimental oral em camundongos. 16 Essa diferença na sobrevida pode estar relacionada à resistência de Brucella, que pode ser maior para algumas cepas do que para outras.…”
Section: Discussionunclassified